الإمام النويري وجهوده في علم القراءات = Al-Imam Al-Nuwayri and his passion in Al-Qiraat - Ahmad Lutfi, Mujahid; Mohamad, Mohammad Redha; Shamsul Kamar, Muhammad Zaid; Mohd Nawi, Mohd Ikram; Ramlan, Muhammad Ammar Farhan (Faculty of Islamic Studies and Civilisation, UIS, 2024)
يهدف هذا البحث إلى معرفة أحد الإمام الجليل في علم القراءات وهو الإمام النويري رحمه الله تعالى، والجهود الذي نال هذا الإمام في هذا العلم. يعتبر مِن أول مَن شرح متن طيبة النشر في القراءات العشر للإمام ابن الجزري رحمه الله تعالى. فكما هو معلوم أن هذه المنظومة من أكبر المصنفات في علم القراءات، حيث استوفى ابن الجزري كلَّ ما يخصّ القراءات في نظم واحد، وكان ملخصًا من كتابه "النشر"، وهو المعروف اليوم بالعشرة الكبرى أو طريق طيبة النشر. يتبيّن من هذا العمل أن الإمام النويري قد عمل جهدًا كبيرًا فيما يتعلق بعلم القراءات. ومما يندرج تحت قضية هذا البحث هو معرفة سيرة الإمام النويري في حياته قبل أن يحصل على هذا القدر العالي في مثل هذا المقام. وقد تمّ ذلك في الاسقراء على مجال مولده ونشأته، ثم رحلاته في طلب العلم، ثم معرفة شيوخه وتلامذته، ومذهبه في العقيدة والفقه. علاوة على ذلك لا بد من معرفة ما صنّف في حياته من المصنفات البديعة في علوم شتى، وخاصة في علم القراءات. ومن ثمّ يظهر لنا أن الإمام النويري قد أثّر إيثارًا بينًا على تنمية علم القراءات لدى الأمة جميعًا، لاسيما من شرحه لمتن طيبة النشر في القراءات العشر. ***** This research aims to explore Al-Imām Al-Nuwayrī which is one of the great scholars in the field of Al-Qirāāt and his contributions to this field. He is considered one of the first scholars to elaborate the Matn "Ṭayyibah al-Nashr Fī al-Qirāāt al-ʿAshr" by Al-Imam Ibn Al-Jazari. It is known that this Matn is one of the largest compilations in the science of Al-Qirāāt, where Ibn Al-Jazarī encompassed all aspects of Quranic readings in one system, summarizing it from his book "Al-Nashr," which is now known as the “Al-ʿAsharah Al-Kubra” or the “Ṭarīq of Ṭayyibah Al-Nashr’. This work demonstrates that Al-Imām Al-Nuwayrī exerted great effort in the field of Al-Qirāāt. One of the aspects addressed in this research is understanding Al-Imām Al-Nuwayrī's biography before achieving such a high status in this regard. This involves exploring his background, upbringing, his pursuit of knowledge, his teachers and students, as well as his beliefs and jurisprudence. Furthermore, it is essential to understand the various remarkable works he authored in the field of Al-Qirāāt. The researcher used the inductive method in this study. Hence, it becomes evident that Al-Imām Al-Nuwayrī had a significant impact on the development of Al-Qirāāt among the entire Muslim community, particularly through his explanation of the Matn “Ṭayyibah al-Nashr Fī al-Qirāāt al-ʿAshr".